A Literature Analysis of Chinese as a Foreign Language Textbook Research in the Past 25 Years: A Visualization Analysis Based on CiteSpace: 近二十五年对外汉语教材研究文献分析——基于CiteSpace的可视化分析 - Amarbayasgalan, Binderiya (Published by Confucius Institute UNS, 2025)
In recent years, with the continuous development of international Chinese education, the field of Chinese textbook research has shown a flourishing trend. Based on the CNKI database, this study employs Cite Space 6.3 R1 software to conduct a bibliometric analysis of literature on Chinese textbooks for foreign learners from 1999 to 2023. The study systematically examines publication volume, key authors, major institutions, research hot spots, and emerging trends. The findings indicate that Chinese textbook research has undergone four stages: the preliminary stage (1999-2005), steady growth stage (2006-2010), peak stage (2011-2018), and stabilization stage (2019-2023). Regarding research hot spots, topics such as textbook compilation, localization, principles of textbook design, and error analysis have gained significant academic attention. Furthermore, keyword clustering and burst word analysis reveal the evolutionary trends of Chinese textbook research, suggesting that future studies may focus more on personalized, intelligent, and multi modal textbook development. This study contributes to a comprehensive understanding of the current state and development trends of Chinese textbook research and provides insights for future investigations.